First record of Telestes pleurobipunctatus (Stephanidis, 1939) in freshwater of Al-Bireh Dam, Wadi Al-Ayoun, Hama, Syria - Razan Hasan Balloul; Mohamad Youns Galiya; Ali Abdullatif Mansour (Journal of Fisheries, 2024)
Despite a large number of studies on freshwater fish fauna in Syrian aquatic habitats lack of data exists for many. This study was conducted in Al-Bireh Dam, located in Wadi Al-Oyoun region, Hama Governorate of Syria and recorded Telestes pleurobipunctatus (Stephanidis, 1939) (Cyprinidae) for the first time. In April 2023, thirteen individuals of the species were caught using local fishing methods. The species is characterised by the presence of a dark band on the sides of the body extending from the front of the snout to the end of the caudal fin, and an orange spot at the base of the pectoral fin. This research sheds light on the qualitative composition of the fish fauna in Al-Bireh Dam Lake, as the species T. pleurobipunctatus is recorded for the first time in Syrian freshwaters.